Keefektifan Metode Problem Solving dan Inkuiri untuk Meningkatkan Kemampuan Berpikir Kritis - Alim Mutaqin; Farhan Saefudin Wahid; Ubaedillah Ubaedillah; Slamet Bambang Riono; Andi Yulianto (Jurnal Kewarganegaraan, 2022)
AbstractThis research aims to: (1) to know the effectiveness of the problem solving method to improve critical ability in IPS subjects; (2) To determine the effectiveness of inquiry methods to improve the ability to be critical in IPS subjects; (3) Describe the difference in the effectiveness of the problem solving and inquiry methods to improve the ability to be critical to the IPS subjects. This type of research uses quasi experiment with pretest-posttest control group design. Data is taken using observation and Test. Analysis of this research data using Anova and Scheefe to test its effectiveness. The results showed: (1) The problem method solving effective to increase the ability of critical thinking by 36% with an alpha value of 68.1519; (2) The inquiry method is effective to increase the ability of critical thinking by 51% with an alpha value of 69.3780; (3) There are differences in the effectiveness of methods problem solving and inquiry to increase the ability of critical thinking on the IPS subjects where the method of inquiry is more effective to improve the ability of critical thinking. So it can be concluded that the use of methods of learning problem solving and inquiry effective to improve students ' critical thinking on IPS subjects in junior high by using interdisciplinary learning approaches, placement Problems as learning objects and the use of learning Facilitias needed during the learning process activities..Keywords: problem solving methode, inquiry methode, critical thinking